CFD-based aeroelastic characterization of streamlined bridge deck cross-sections subject to shape modifications using surrogate models - Cid Montoya, M.; Nieto, F.; Hernández, S.; Kusano, I.; Álvarez, A.J.; Jurado, J.Á. (Journal of wind engineering and industrial aerodynamics, 2018)
The classical approach currently used in the bridge engineering industry for the structural and aeroelastic design of bridges is based on an iterative heuristic process which includes wind tunnel testing. The dependency on experimental techniques for the aeroelastic characterization of the bridge deck cross-section requires a substantial amount of resources, and consequently the number of potential candidate designs must be limited. The fast improvements in Computational Fluid Dynamics (CFD) techniques in recent years have led to its use in the industrial field, and consequently bridge design methods must be updated. This paper proposes a fully numerical strategy to overcome the classical iterative process in bridge deck shape design. Firstly, it consists in constructing a surrogate model of the aerodynamic response of the baseline cross-section and the allowed shape variations by conducting a set of CFD simulations of several sample designs. Then, the force coefficients and their slopes can be obtained for every design included in the design domain, the flutter derivatives can be approximated by the quasi-steady formulation, and the flutter velocity can be computed. This procedure is applied to two cable-stayed bridges with different spans, and the reported results are validated with wind tunnel tests. •Full computational approach to aeroelastic characterization of streamlined decks is proposed.•The aerodynamic effects caused by shape variation are assessed by means of surrogate models.•Width and depth dimension of the deck control aeroelastic responses.•Complete experimental validation of the proposed numerical methodology is provided.